PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW UNTUK MENINGKATKAN HASIL BELAJAR MATERI SISTEM PENCERNAAN MANUSIA PADA SISWA KELAS VIII A SMP NEGERI 1 KAMBERA - Agata Lemba Eut; Yohana Makaborang; Yohana Ndjoeroemana (Universitas Bhinneka PGRI, 2023)
The research was conducted with the aim of knowing student learning outcomes using the Jigsaw cooperative learning model on the subject of the human digestive system at SMP Negeri 1 Kambera. This research is a Classroom Action Research (PTK) consisting of pre-cycle activities, cycle 1 and cycle 2, with a total of 32 students. Each cycle consists of four stages, namely planning, implementing, observing, and reflecting. In pre-cycle activities, it was found that overall student learning outcomes were 56.0%, the number of students who completed 4 students with a percentage of 12.5% and those who did not complete were 28 students with a percentage of 87.5%. Furthermore, in cycle 1, student activities consisting of affective aspects included 11 students with good predicates and 21 students with sufficient predicates. Then the learning outcomes in cycle 1 mean the average value of all students is 67.1 students who complete consist of 12 people with a percentage of 37.5% who do not complete consisting of 20 people with a percentage of 62.5%. In cycle 2 affective there were 15 students with very good predicates and 17 students with good predicates. Learning outcomes in cycle 2, the average value of all students is 82.0 students who complete consist of 29 students with a percentage of 90.6% and students who do not complete consist of 3 students with a percentage of 9.3%. Thus it can be concluded that the application of the jigsaw cooperative learning model to improve learning outcomes of the human digestive system material in class VIII A students of SMP Negeri 1 Kambera.